Antioxidant, anticancer and ACE-inhibitory activities of bioactive peptides from wheat germ protein hydrolysates. (December 2019) - Karami, Zohreh; Peighambardoust, Seyed Hadi; Hesari, Javad; Akbari-Adergani, Behrouz; Andreu, David
Abstract: Hydrolysates of wheat germ protein prepared with Alcalase, pepsin or proteinase K had significant antioxidant activities and the ability to decrease A549 cell viability in a concentration-dependent manner. Hydrolysates were fractionated using RP-HPLC and the antioxidant activity of fractions was evaluated as ABTS radical scavenging activity. Fractions with the highest activities were further analyzed using LC/ESI-MS/MS. Two peptides, KELPPSDADW and SSDEEVREEKELDLSSNE of the pepsin hydrolysates, three peptides, TVGGAPAGRIVME, VGGIDEVIAK and GNPIPREPGQVPAY of the Alcalase hydrolysates, and two peptides SGGSYADELVSTAK and MDATALHYENQK of the proteinase K hydrolysates were identified as the main components. Replicates of these peptides were made using solid phase synthesis and further biological activities, including antioxidant, ACE inhibitory and cytotoxic activities were evaluated. Peptides with the highest activities were KELPPSDADW (antioxidant), SGGSYADELVSTAK (ACE inhibitory) and SSDEEVREEKELDLSSNE (cytotoxic). Graphical abstract: Image 1 Highlights: Defatted wheat germ protein was hydrolyzed using Alcalase, Pepsin or Proteinase K. Peptides with antioxidant, ACE inhibitory and cytotoxic activities were identified using nano-LC/ESI-MS/MS analysis. The peptides have potential applications as functional food additives to improve human health.